BEST PRACTICES IN ENGLISH TEACHING AND LEARNING IN HIGHER EDUCATION Lessons from Hong Kong for Global Practice - Wong, Lillian L. C. (Routledge, 2024)
Lillian Wong brings together evidence-informed studies which are at the forefront of higher education developments in English language teaching and learning and shares expertise from prominent academics in Hong Kong. Written by experienced practitioners who are active in the evolving field of scholarship of teaching and learning, it provides accessible and engaging insights into best practices in new and innovative areas, such as communities of practice, scholarship, big data analytics, digital literacies, blended learning, small private online courses, dialogic use of exemplars, students as tutors, and critical thinking. The book covers best practices in three interrelated key areas in university English language education, including curriculum design and pedagogy, use of technologies, and teaching and learning English in the disciplines. Linking theory and practice, the chapters discuss the emphasis on EAP/ESP in university English language education, how technological developments are impacting the field and the implications for further research and teaching of English in higher education. This resourceful collection is essential reading for teachers in-service and in-training, or those working in language education at the tertiary level where English is being used as an academic lingua franca, a medium of instruction or where EAP/ESP plays an important role. Researchers in TESOL and applied linguistics, curriculum designers and leaders, teacher educators and policy makers as well as undergraduate and postgraduate students will also find it valuable.